O ATENDIMENTO AO ALUNO SEMI-RETORNADO: PROPOSTAS DE MODIFICAÇÕES QUALITATIVAS NO ÂMBITO DA EDUCAÇÃO DAS ESCOLAS MUNICIPAIS CORUMBAENSES. - GILMAR FERNANDES MARTINS (2023)
The objective of this study is to analyze the educational context of municipal schools on the international border between Brazil and Bolivia, in the city of Corumbá MS. The approach to this theme is made from the perspective of assisting international migrant students residing in the border area, which must be effectively successful, due to the dynamism and effervescence that are constant in the border region. It should be noted that Bolivian commuting migration takes on daily contours as a result of the need for Bolivian migrants to access, mainly, the public services offered on the Brazilian side of the border. The migratory circulation of Bolivians on the Corumba border transforms the relations between these and the Brazilians, such situations need to be detailed and studied, in order to compose an understanding that reveals the ethnicity built at each border crossing. The objective is to identify the characteristic traits of commuting in the border region. Acclimating itself to the educational characteristics that are necessary to achieve good service to international migrant students. In short: care is taken to ensure that students who study at Corumba schools are served in an exemplary manner, whether they are Brazilians or international migrants. It was also necessary to analyze international migration within the Corumba border, highlighting the cases of migrants from Haiti and Venezuela. In this wake, a first analysis of the reception process for international migrants in the city of Corumbá MS was launched.